Stabilisasi Tanah Lempung dengan Campuran Fly Ash dan Serbuk Batu Karang terhadap Nilai CBR - Try Sunanda Fathanah; Duha Awaluddin Kurniatullah; Alfian Adie Chandra (Jurnal Sipil Terapan, 2024)
Clay soils generally have low bearing capacity and are vulnerable to the water. Therfore, stabilization is necessary as an effort to increase the bearing capacity and improve the other parameters, one fo them by adding other materials such as fly ash and coral limestone powder as done in this research. The purpose of this research is to understand the effect of fly ash and coral limestone powder addition to the bearing capacity of clay soils after compaction process in term of CBR value by adding 15% fly ash and 0%, 10%, 20%, 30% coral limestone powder variations. The analysis results show that the original soil is an inorganic clay with 47,84% plasticity index. By adding fly ash and coral limestone powder variations decreases the plasticity index value to the lowest value 20,23%. The specific gravity increased on the 15% fly ash addition from 2,63 to 2,868 and decreased along with coral limestone powder addition to the lowest value 2,556. The maximum dry density decreased by adding 15% fly ash from 1,465 gr/cm3 on the original soil to 1,450 gr/cm3 and increased along with coral limestone powder addition to the highest value 1,522 gr/cm3. The optimum moisture content decreased along with the fly ash and coral limestone powder addition from 26,80% to 20,50%. The CBR value increased from the lowest value 0,47% to the highest value 15,29%.